Application of computational fluid dynamics in subway environment without fire and smoke—Literature review. (December 2021) - Peng, Yunlong; Gao, Zhi; Ding, Wowo; Zhang, Jianshun; Li, Xiaozhao; Xu, Jinfeng; Wei, Yanli
Abstract: As more megacities emerge owing to urbanization and industrialization, the subway has become the main public transportation mode worldwide, providing punctuality and convenience. The subway environment, including its ventilation, thermal comfort, air quality, and energy consumption, remains an area of great focus for scientists and passengers. In addition to theoretical and experimental methods, computational fluid dynamics (CFD) has been used in past decades to predict 3D airflows, temperatures, and pollutant dispersion in subway tunnels, stations, and cabins. In this review, recent applications of CFD involving three scenarios—subway tunnels, stations, and passenger cabins—and two objective parameters—particulate matter, and energy savings till 2021—are systematically presented. The boundary conditions, validation methods, turbulence models, and mesh information are summarized. Finally, the possibilities regarding novel models, open-source CFD codes, and best practice guidelines are discussed with the aim to predict future perspectives on the subway environment.